Employing pockets in decorating children's clothes (Journal of the College of Basic Education, 2022)
The research is summarized in clarifying the importance of decorating baby clothes and its importance for implementing different designs and models for children at different ages and its importance in helping the child to save his small things and achieve his desire to have his own secrets , that he maintained and unique The research consist of four chapters . chapter one include a show for the research problem and its significance then the object (goal) of the research and its borders and determine the most important terms used in . chapter two is clarifying the theoretical side and address the most important types of pockets and how it used. the third chapter includes the practical side, in this chapter ten models of pockets were selected and preparing a group of experts in sewing to determine its suitability and fitness for children's clothing Chapter four is showing the most important findings that the researcher has reached , then mentioning the recommendation , proposals and a list of the scientific sources in the research